In vivo three-dimensional kinematics of the cervical spine during maximal active head rotation - Kang, Jian (PLoS One, 2019)
OBJECTIVE: The aim of this study was to measure the movement of the cervical spine in healthy volunteers and patients with cervical spondylosis (CS) and describe the actual motion of the cervical spine using a three-dimensional (3D) CT reconstruction method. The results can enrich current biomechanical data of cervical spine and help to find the differences between the noted two groups. MATERIALS AND METHODS: 20 healthy volunteers underwent CT examination ranging from the clivus of the occiput (Oc) to the top of first thoracic vertebrae (T1) in a neutral position with left or right maximal axial rotation, while 26 CS patients received the same CT scan procedures in the neutral position with left and right maximum rotation. Subsequently, the three-dimensional images of the occiput and every cervical vertebrae (C1-C7) were reconstructed using medical software. 3 virtual non-collinear markers were placed on the prominent structures of foramen magnum and every cervical vertebrae. Then, the 3D orthogonal spatial coordinates were defined with these anatomical markers to represent the orientation and position of every vertebra. Segmental relative motions were calculated using Cardan angles in the 3D spatial coordinates. Finally, the differences between the two groups were analyzed with statistical software SPSS. RESULTS: The cervical spine exhibited complicated 3D movements, which could be adequately described using the three-dimensional CT reconstruction method. Reliability analysis of the 3D CT reconstruction method showed inter-rater ICC of 0.90–0.99 and intra-rater ICC of 0.91–0.98, suggesting very good consistency. Besides, the rotation at the upper cervical spine (Oc-C2) took up at least 60% of the total cervical rotation. The coupled lateral bending movement of the upper cervical spine was opposite to the major motion, while the movement of the lower cervical spine followed the same direction as that of the major motion. Oc to C5 segments were all coupled with the back-extension movement. The relative translations of all adjacent segments in each direction were minimal. CS patients showed a significant decrease in the movement of the C4-C5 segment compared with healthy volunteers. CONCLUSION: The motion of the cervical spine was complicated and three-dimensional. The CT reconstruction method employed here was good at describing such movement. The 3D CT reconstruction method exhibited high reproducibility when measuring cervical spine movement. CS patients and healthy volunteers showed significant differences in the movement of some segments.